MAKNA HADIS LARANGAN BERHUBUNGAN SEKS SAAT ISTRI HAID DAN RELEVANSINYA BAGI KESEHATAN (KAJIAN TAKHRIJ HADIS) - Aulia, Fitri; Hasyim, Ahmad Faqih; Hartati, Hartati (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2023)
The Hadith of the Prophet SAW not only discusses matters related to worship, faith, muamalah, and so on, but also explains a lot about the biological condition and nature of a woman, one of which is menstruation. Among other things, the Prophet said that it is forbidden for women who are menstruating to have intercourse with their husbands. The purpose of this study is to determine the quality and quantity of hadiths and find out the meaning of the hadith prohibiting sex during menstruation from medical science. The method used in conducting this research is a qualitative method, by describing the theories and uncovering the meaning of the hadith which prohibits having sex during menstruation. While the type of research used in the preparation of this thesis is using Library Research. The results of this study indicate that the hadith narrated by Ibn Majah with number 639 is of á¹£ahÄ«h li Å¼atihi quality. As for the quantity, this hadith is included in the gharib mutlaq hadith. The meaning behind the prohibition of this hadith is that it can cause sexually transmitted diseases such as epididymitis and orchitis, cervical cancer, endometriosis, ovarian cancer, vaginal cancer, vulvar cancer, HIV/AIDS, trichomoniasis, herpes simplex, and genital warts.